Bentuk Dan Gerak Tari Tradisional Manuk Beberi - Muh Ridwan Markarma; Riyana Rizki Yuliatin; Hary Murcahtanto; Ummi Risti Ayuni Rahman; Nur Aetin Mahi Sofiana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The purpose of this study was to describe the various forms and movements of the Manuk Beberi dance. This research uses descriptive qualitative methods using theories related to the research topic. The theory used is the theory of symbols which is translated into discursive and presentational symbols. The results showed that the Manuk Beberi dance is a regional dance originating from Lombok, West Nusa Tenggara. The Manuk Beberi dance was created based on the story of Dewi Anjani's pet. This dance is danced by two male dancers with energetic movements that reflect the character of Dewi Anjani's pet chicken. The various movements of the Manuk Beberi dance are classified into discursive symbols and presentational symbols. Movements that are included in the discursive symbol are the movements of the Keber, Notok, Ngaeh and Bekupu. These movements have certain meanings based on the results of mutual agreement in an area. Meanwhile, other Manuk Beberi dance movements are included in the presentational symbol, namely movements that are only complementary and do not have a core meaning. In conclusion, the traditional dance of Manuk Beberi has four forms, namely, the traditional dance form, which is the pet movement of Dewi Anjani. Keywords: Form, Manuk Beberi Dance, Motion